Pemberian Bantuan Bencana Alam Tanah Lonsor Kampung Mbenti Distrik Minyambouw - Zulkarnain; Lilis Indrayani; Yammes J Batkunde; Sabinus Rainer N. Chiristi; Engelbert Worabai; Samuel Mathias Dauth Menai; Melvi Marhaba; Melva Marhaba (AMMA : Jurnal Pengabdian Masyarakat, 2024)
This Community service activities "Provision of Natural Disaster Assistance for Landslides in Mbenti Village, Minyambaouw District" were carried out on July 1, 2024. The activity was carried out as a form of concern from lecturers and students of STMIK Kreatindo Manokwari for the victims of the landslide. The assistance distributed was in the form of basic necessities and clothing. The purpose of this community service activity is to help ease the material and moral burden of the victims of the landslide. The activity was divided into two stages, namely: fundraising and distribution of assistance. The results of providing assistance to the community were very happy and enthusiastic in receiving assistance and the victims were able to raise a new spirit in being active in the midst of the landslide that hit.